Investigation of the void fraction of gas-liquid two phase flow in vertically-upward channel / Nur Afiqah Adilah Muhamad Khosim - Nur Afiqah Adilah , Muhamad Khosim (2019)
Void fraction is an important process variable for the volume and mass computation required for transportation of gas-liquid mixture in pipelines, storage in tanks, metering etc. Inaccurate measurement would introduce errors in product measurement with potentials for loss of revenue. Accurate measurement is often constrained by invasive and expensive online measurement techniques. This work focuses on the use of Constant Electric Current Method (CECM) using specially developed sensor to measure void fraction in a vertically arranged gas-liquid two-phase flow channel. The effects of velocities of both phases were examined with variety of combinations using an industrial scale two-phase flow loop. The results show that at a constant rate of liquid superficial velocities, the void fraction increases with the increasing gas superficial velocities and at a higher velocity of liquid phase, the value of void fraction becoming lower. Besides, at lower liquid superficial velocity, the void fraction at the upper side of flow channel is higher than the lower position. However, when the liquid phase dominates the flow channel at higher liquid superficial velocity, and when the gas superficial velocity is further increased, the flow become chaotic and a rough turbulent condition has developed, and therefore void fraction can be seen fluctuating up and down at the higher position.